Ischiofemoral impingement syndrome: an overview for strength and conditioning professionals - Vogrin, M.; Licen, T.; Kljaic Dujic, M. (Strength and Conditioning Journal, 2021)
Ischiofemoral impingement (IFI) is a hip condition associated with the entrapment of the quadratus femoris muscle between the ischiofemoral space and the lesser trochanter of the femur. As an overlooked cause of hip pain, it is often confused with other injuries (e.g., deep gluteal syndrome and proximal hamstring tendinitis), with S&C professionals and rehabilitation specialists being generally unaware of its existence. Therefore, the aim of this article is to present an overview of IFI, which includes diagnosis, injury mechanisms, and conservative treatment options.